Medusa as the story of Victorian feminine identity - Avarvarei, Simona Catrinel (Journal of History Culture and Art Research, 2015)
Medusa as the story of Victorian feminine identity Abstract This paper scans the meandering paths of a quest through the realms of womanly self and its articulateness in (robust) constructs of individuality. We have departed from a paradigm of interpretation related to a mythological figure, dual in itself, namely the Medusa, perceived as either mask, or face – which has always fascinated with her tragic beauty. It is within the semantics of the word fascinum – charm, evil spirit but also virile member – where the attributes of an age, the Victorian time, that was equally fascinating, as it was whirling and powerful, lie hidden. This paper focuses on artistic reflections of Victorian femininity in an effort to examine how it contributed to the ever-changing definition and search of female gender identities at times of hegemonic masculinities. Art and fiction articulate some of the more powerful challenges. If philosophy encapsulates phallogocentrism, as Derrida points out, fiction, he claims, is an invagination, namely a creation of differences where no term spells self-sufficiency.